Порівняльний аналіз методів розв’язання задач ідентифікації - Тимченко, А.А.; Бойко, В.В.; Скоробрещук, В.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
In the article a comparative analysis of the methods of identification tasks solution is made. Three approaches are considered determinate approach based on the method of selected points; statistical approach which includes least-squares method; and inductive approach - Group Method of Data Handling. A number of experiments based on model structural optimization are carried out. In the process of the analysis of obtained models the method of optimal complexity is found. The examined system flow diagram can be successfully for intricate analytical problems solution.